2020
DOI: 10.1007/978-3-030-50232-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Exclusion Issues of Mobility-as-a-Service (MaaS): The Potential Problems of Older Travellers’ Involvement

Abstract: A series of pilots and service fragments of Mobility-as-a-Service have launched out in recent years, but it is generally recognized as is still on the early stage of its development, whether in terms of the service concept and framework, the level of urban construction and the acceptance of travellers. According to the earlier study of MaaS in a workshop in middle England, the result referred to the lack of consensus and mismatch of value propositions among stakeholders, which leads to the early market has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Concerns have been raised regarding the ability of MaaS to cover the needs of groups within the business-driven market landscape. It is underscored that, for older travellers, a MaaS system can potentially create accessibility barriers due to challenges of certain groups in adapting to new technologies and changes [36]. On the other hand, it has been found that younger people positively view aspects of MaaS such as the provided flexibility in transport, but express concerns and reservations regarding shared transportation modes [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerns have been raised regarding the ability of MaaS to cover the needs of groups within the business-driven market landscape. It is underscored that, for older travellers, a MaaS system can potentially create accessibility barriers due to challenges of certain groups in adapting to new technologies and changes [36]. On the other hand, it has been found that younger people positively view aspects of MaaS such as the provided flexibility in transport, but express concerns and reservations regarding shared transportation modes [37].…”
Section: Literature Reviewmentioning
confidence: 99%